The structural and surface properties of natural and modified coal gangue. (1st April 2017) - Jabłońska, Beata; Kityk, Andriy V.; Busch, Mark; Huber, Patrick
Abstract: A novel application of coal gangue as inexpensive adsorbents is considered in this study. The structural and surface properties of natural and modified gangue were studied via nitrogen adsorption. Four types of samples were studied: natural, modified with H2 NO3 and H2 O2 and calcined at 250 °C and 600 °C. The specific surface area and porosity of the samples were determined using various methods. The raw material is mainly mesoporous with relatively small specific surface area. The chemical modification enlarged the total pore volume and the specific surface area. The calcination at 250 °C enlarged slightly the pore volume and lowered the specific surface area, but did not cause significant changes in the structural properties. The calcination at 600 °C resulted in a significant increase in pore volume and a decrease in specific surface area. These results suggest that the coal gangue studied here could be used as inexpensive adsorbent in industrial wastewater pretreatment. Graphical abstract: Highlights: Using coal gangue as inexpensive adsorbent is considered. The surface properties of coal gangue were studied via nitrogen adsorption. The natural gangue, modified with H2 NO3 + H2 O2 and calcined at 250/600 °C was tested. The gangue contains mainly small mesopores. The surface area was largest for gangue modified with H2 NO3 + H2 O2 .